Artificial decision-making and artificial ethics: A management concern - Khalil, Omar E. M. (1993)
Expert systems are knowledge-based information systems which are expected to have human attributes in order to replicate human capacity in ethical decision making. An expert system functions by virtue of its information, its inferential rules, and its decision criteria, each of which may be problematic. This paper addresses three basic reasons for ethical concern when using the currently available expert systems in a decisions-making capacity. These reasons are (1) expert systems' lack of human intelligence, (2) expert systems' lack of emotions and values, and (3) expert systems' possible incorporation of intentional or accidental bias. For these reasons artificial ethics seems to be science fiction. Consequently, expert systems should be used only in an advising capacity and managers should not absolve themselves from legal and ethical responsibility when using expert systems in decision making.
Keywords: Decision Criterion; System Function; Expert System; Economic Growth; Decision Making